Effectiveness of a protocolized dispensing service in community pharmacy for improving patient medication knowledge - Abaurre-Labrador, R.; Maurandi-Guillén, M.; García-Delgado, P.; Moullin, Joanna; Martínez-Martínez, F.; García-Corpas, J. (Springer Netherlands, 2016)
© 2016, Springer International Publishing. Background Sufficient patient medication knowledge is essential for appropriate use. The dispensing service provided in community pharmacies is one method that may be used to educate patients on their medications. Objective To compare the effectiveness of protocolized dispensing (following a dispensing protocol that includes standardized patient education), with the effectiveness of traditional dispensing (provision of medication without standardized patient education and information provided only if directly requested), for improving patient medication knowledge. Method Pre-post quasi-experimental study of patients or caregivers over 18 years of age requesting one or more medications for their own use or for others. The intervention consisted of using a protocolized process for dispensing medicines in a community pharmacy. The association between the dispensing effectiveness (patient medication knowledge pre and post dispensing) and predictor variables was studied using a multivariate binary logistical regression model. Results In total 661 participant medication requests were included in the study. Protocolized dispensing was more effective than traditional dispensing for improving medication knowledge (OR 2.390; 95 % CI 1.373–1.162). Conclusion As a means to improve patient medication knowledge it may be recommended that protocolized dispensing processes should be developed, evaluated and implemented with the ultimate aim of improving the appropriate use of medicines.